Separating Empty and Full Recombinant Adeno‐Associated Virus Particles Using Isocratic Anion Exchange Chromatography. Issue 1 (19th October 2020) - Dickerson, Ryan; Argento, Christopher; Pieracci, John; Bakhshayeshi, Meisam
Abstract: The development of recombinant adeno‐associated virus (rAAV) gene therapies is becoming an increasing priority in the biotherapeutic landscape. One of the challenges associated with the production of rAAV is the formation of empty AAV particles that do not contain a therapeutic gene. The concerns about the impact of empty particles on clinical safety and rAAV‐mediated gene expression have necessitated the development of purification processes to remove these species. The development of a robust and scalable purification process to separate empty and full AAV particles at large scale remains a challenge. In this study, a novel anion exchange chromatography process based on isocratic wash and elution steps to enrich full rAAV2 particles is presented. An operating design space is identified to ensure the robustness of the process. The isocratic chromatography provides several advantages over the traditional shallow linear gradient elution, including lower buffer consumption, smaller intermediate pool volumes, and more robust manufacturing. Abstract : Robust and scalable separation of empty particles from recombinant adeno‐associated virus (rAAV) vectors is key in rAAV production. This separation is currently achieved via linear gradient elution chromatography which is challenging to implement at large scale. Improved separation resolution is demonstrated between the empty and full particles by combining NaCl and MgCl2 as eluents, enabling an isocratic anion exchange chromatography separation.